A Systematic Literature Review on Civic Engagement Form among Youth: Online Participation - Anuar Kamri, Khairol; Md Yusoff, Rosman; Fauzi Ahmad, Md; Syahid Mohd Ali, Adi; Nizam Attan, Mohd; Sobhi Ishak, Mohd; Mahadee Ismail, Mohd (International Journal of Psychosocial Rehabilitation, 2019)
Digital citizenship is mushrooming among youth. The usage of the internet among them is high, as is time spent on the online network as well. This systematic review article presents what are the online participation activities among youth that help them to connect with civic engagement and enhance their awareness about public issues. The methodology used in this systematic literature review is guided by Preferred Items for Systematic Reviews and Meta-Analysis Guidelines. 38 articles from Scopus as the main database and Google Scholar as the supported database were selected through the process of identification, screening, eligibility, and inclusion/exclusion. Nine main themes are found as a result, but this article focuses on the online participation theme as civic engagement among youth. The online participation theme was examined, which resulted in five main activities, which are information sharing, online networking, civic content creation, active participation, and usage of other digital platforms. The analysis on online participation also found that focus is given more to social media contribution but lack in other digital technologies platform benefit. Future literature is recommended to focus more on how other digital platforms can contribute to civic engagement among youth and finally result in forming good citizenship.